Systematic evaluation and metallurgical process for complex sulphide ores of gold - Sánchez Quispe, Luis (2013)
Peru, which is a rich country in amount of ores and gold reserves, moreover; it has an attractive minerals sector to the world and of great importance in national economic development. However, in the metallurgy of gold ores, there are minerals called refractory or complex, where free fine gold is trapped or associated with sulfides (pyrite and arsenopyrite), this problem can be seen in the concentrator Tamboraque, which uses inefficient conventional metallurgical processes and of high operating costs. Hence, the present research found an alternative treatment for this type of complex mineral, consisting in a total flotation in a first stage and then a special differential flotation in the second stage, obtaining as a result a reduction of 76.82 % treatmentvolume, 78.31 % the consumption of reagents, 63.64 % presence of toxic reactive in general tailings, 55.85 % and 55.04 % the volume of water and operating expenses used in flotation circuits in thereof. Furthermore, it was determined that a minimum investment of U.S. $ 406,160.73, this proposal can be implemented using only their own facilities and resource, and significant advantages in the environmental, technical and economic aspect.